Analisis Strategi Promosi Untuk Meningkatkan Penjualan Pada Mardhiyyah Ritel - Fauziah Utami (STIE Amkop Makassar, 2024)
This research was conducted at Mardhiyyah Retail. Mardhiyyah Retail is a business in the service and supermarket sector whose aim is to sell goods or products that have been produced by producers for resale to the public. Mardhiyyah Retail was founded in 2009, located at Kiara Sari Asri Housing, Jl. Kiara Sari Raya no. 6, Bandung. The purpose of this research is to find out what promotional strategies are carried out by Mardhiyyah Retail so that it can increase sales. In this research, researchers used a qualitative descriptive approach by collecting data through observation, interviews and documentation. The informants in this research consisted of 1 (one) key informant and 1 (one) comparison informant. The results of this research state that the role of word of mouth promotion is able to support increased sales at Mardhiyyah Retail. The prices offered by Mardhiyyah Retail also play a role in the success of the promotional strategy created because the prices offered are competitive with the market. Using delivery messages via business WhatsApp messages can also provide opportunities to increase sales. So this promotional method can increase sales at Mardhiyyah Retail.